2015
DOI: 10.1002/jmv.24325
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus is present in the neonatal intensive care unit

Abstract: Nosocomial transmission of respiratory syncytial virus (RSV) occurs in children within the neonatal intensive care unit (NICU). During peak community RSV transmission, three swabs were collected from the nose, hand and personal clothing of visitors and health care workers (HCW) in NICU once every week for eight weeks. Nasal swabs were collected from every third neonate and from any neonate clinically suspected of having a respiratory infection. Environmental sampling of high touch areas was done once during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…While these interventions were associated with reducing transmission events in our NICU, they did not eliminate respiratory viruses. There are likely multiple 'portals of entry' for respiratory viruses, including unrecognized ill visitors and HCP, adults who are infectious prior to the onset of symptoms, and/or asymptomatic adult or infant carriers shedding viruses [4,27].…”
Section: Discussionmentioning
confidence: 99%
“…While these interventions were associated with reducing transmission events in our NICU, they did not eliminate respiratory viruses. There are likely multiple 'portals of entry' for respiratory viruses, including unrecognized ill visitors and HCP, adults who are infectious prior to the onset of symptoms, and/or asymptomatic adult or infant carriers shedding viruses [4,27].…”
Section: Discussionmentioning
confidence: 99%
“…11,12 The human body is home to a diverse community of microorganisms, primarily bacteria, 38 but also fungi 39 and other organisms. Clothing can also contain microorganisms such as bacteria [40][41][42] and viruses 43 that, together with bacteria-laden skin flakes, fragments and fibers, get dispersed to the surroundings via occupants' activities owing to frictional forces involving fabric fibers, external contact surfaces, and/or the wearer's skin. 15,19,44,45 Increasing evidence identifies human occupancy as an important source of airborne bacterial and fungal DNA in indoor air.…”
Section: Importance Of Human Envelope Shedding For Exposure Assessmentmentioning
confidence: 99%
“…Nosocomial transmission of respiratory viruses occurs and is a consideration when implementing policies around cohorting of patients with CF. An Italian study tested hospital air and environmental surfaces of toilets for RV, and it was not detected, however, previous studies have identified influenza and respiratory syncytial virus in samples of hospital air and surfaces …”
Section: Introductionmentioning
confidence: 97%
“…An Italian study tested hospital air and environmental surfaces of toilets for RV, and it was not detected, 7 however, previous studies have identified influenza and respiratory syncytial virus in samples of hospital air and surfaces. [8][9][10] We carried out a study to investigate the RV infections present in a cohort of children with CF who attended a CF outpatient clinic in Sydney, Australia. The aims of this study were to determine whether RV was correlated with exacerbations in a cohort of children with CF, and whether a particular strain of RV was associated with exacerbation.…”
Section: Introductionmentioning
confidence: 99%